Informational Profiles and Incidental Consumption Pathways: A model to analyze the relationship of young people with the news - Gómez Astudillo, Rocío; Benavides Almarza, Cristóbal (Estudios sobre el Mensaje Periodístico, 2026)
In the context of news consumption on social media, incidental exposure has been identified as one of the predominant practices for encountering news, especially among young people. Despite the exploration of its characteristics in existing studies, there is a need to understand its development in greater depth and to examine the differences that emerge according to audiences' news reports. This research proposes a model that links news profiles of young people aged 18 to 24 living in the Metropolitan Region of Chile with the type of pathway of incidental consumption. The model is based on a mixed-methods approach, which included 40 interviews and 385 surveys. Incidental consumption refers to the activities that people engage in when they come across news in this way. The results of the study indicate that the consumption habits of young people regarding news can be classified into three distinct profiles. The following categories are proposed for consideration: "social media news users", "minimalists" and "digital traditionalists". Moreover, three potential courses of action have been identified in the aftermath of incidental encounters: the scrolling of content due to a lack of interest or to avoid news updates; the partial review of content by reading headlines or descriptions; and the development of four intentional search strategies. These findings offer a more profound comprehension of informational practices that have the potential to inform new research directions and be of use to industry decision-makers seeking to enhance their engagement with their audiences.
Keywords: Consumption profiles; incidental consumption; news consumption; young people; social media